Schizophrenia, dissociation, and consciousness - Bob, Petr; Mashour, George A (Consciousness and cognition, 2011)
Current thinking suggests that dissociation could be a significant comorbid diagnosis in a proportion of schizophrenic patients with a history of trauma. This potentially may explain the term "schizophrenia" in its original definition by Bleuler, as influenced by his clinical experience and personal view. Additionally, recent findings suggest a partial overlap between dissociative symptoms and the positive symptoms of schizophrenia, which could be explained by inhibitory deficits. In this context, the process of dissociation could serve as an important conceptual framework for understanding schizophrenia, which is supported by current neuroimaging studies and research of corollary discharges. These data indicate that the original conception of "split mind" may be relevant in an updated context. Finally, recent data suggest that the phenomenal aspects of dissociation and conscious disintegration could be related to underlying disruptions of connectivity patterns and neural integration.
Keywords: magnetická rezonanční tomografie; schizofrenie; Consciousness; nervové dráhy; schizofrenie (psychologie); Brain; Magnetic Resonance Imaging; Dissociative Disorders; Neural Pathways; mozek; Humans; neurozobrazování; Neuroimaging; Schizophrenia; disociační poruchy; vědomí; Schizophrenic Psychology; lidé